DETERMINING THE MARKETING STRATEGY OF LOKALATE USING SWOT ANALYSIS METHOD - Jocom, Alexander Abieza Pinem; Frianto, Agus (Yayasan Education and Social Center, 2024)
This research aims to determine what marketing strategy can be applied at Lokalate brand using SWOT analysis. This research uses a descriptive methodology by looking at the historical data from 2022. Data collection is acquired from secondary data and observation conducted on the brand environment. The data collected was then analyzed using the IFAS, EFAS, and the SWOT matrix. The result showed that the IFAS matrix obtained a strength value of 1,625 and a weakness value of 0,875. Indicates that the Lokalate brand utilizes more Strength rather than the weakness value. The EFAS matrix obtained an opportunity value of 1,5 and a threat value of 0,875, which indicates that the Lokalate brand occupies more significant opportunities than threats. Based on the SWOT analysis quadrant, Lokalate is in the first quadrant. Is the appropriate strategy for Lokalate to utilize its Strength and take advantage of any existing opportunities